Implementasi metode brainstorming dalam implementasi pembelajaran pendidikan agama islam pada siswa SMA di Bukittinggi - Pratama, Andy Riski (LP2M STAI Darul Kamal NW Kembang Kerang NTB, 2022)
The background of this research is because students are still lacking in the learning process, especially in Islamic Religious Education subjects at SMA Negeri 4 Bukittinggi. The purpose of this research is to find out how successful the implementation of the Brainstorming method is in Islamic Religious Education subject matter Syaja'ah and its relation to the problem of moral degradation today in class XI SMA Negeri 4 Bukittinggi. This research was conducted through a qualitative descriptive type approach using key informants, namely Islamic Religious Education subject teachers and supporting informants were class X students. In collecting data the authors used observation and interview data to test the accuracy of the data. Based on the results of the study there are obstacles in the application of the Brainstorming method to learning Islamic Religious Education, the use of the Brainstorming method cannot be applied optimally, in practice it is not in accordance with the steps of the Brainstorming method